Performance Analysis of a Booster Pump for Increasing Fluid Flow Rate - Putra Ramadhan; Mukhnizar Mukhnizar; Zulkarnain Zulkarnain (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The booster pump is a type of dynamic pump designed to increase pressure and flow rate in a clean water distribution system. This study aims to analyze the performance of a booster pump in increasing fluid discharge in the Padang City Regional Drinking Water Company (PERUMDA). The analysis focuses on the relationship between total head, pressure loss, and pump power to determine the effectiveness of the booster pump compared to a conventional centrifugal pump. The results showed that the booster pump increased discharge from 0.067 m³/s to 0.0833 m³/s, achieving a total head of 42.3 m. The required hydraulic power was 43.75 kW, with an efficiency of 79.07%. The analysis indicated that friction and elbow losses totaled 25.56 m, decreasing as the elbow angle was reduced. Overall, the booster pump effectively enhanced both fluid discharge and pressure with minimal power increase.